LPA2 Contributes to Vascular Endothelium Homeostasis and Cardiac Remodeling After Myocardial Infarction. Issue 5 (3rd August 2022) - Pei, Jianqiu; Cai, Lin; Wang, Fang; Xu, Chuansheng; Pei, Shengqiang; Guo, Hongwei; Sun, Xiaogang; Chun, Jerold; Cong, Xiangfeng; Zhu, Weiquan; Zheng, Zhe; Chen, Xi
Abstract : Rationale: Myocardial infarction (MI) is one of the most dangerous adverse cardiovascular events. Our previous study found that lysophosphatidic acid (LPA) is increased in human peripheral blood after MI, and LPA has a protective effect on the survival and proliferation of various cell types. However, the role of LPA and its receptors in MI is less understood. Objectives: To study the unknown role of LPA and its receptors in heart during MI. Methods and Results: In this study, we found that mice also had elevated LPA level in peripheral blood, as well as increased cardiac expression of its receptor LPA2 in the early stages after MI. With adult and neonate MI models in global Lpar2 knockout ( Lpar2 -KO) mice, we found Lpar2 deficiency increased vascular leak leading to disruption of its homeostasis, so as to impaired heart function and increased early mortality. Histological examination revealed larger scar size, increased fibrosis, and reduced vascular density in the heart of Lpar2 -KO mice. Furthermore, Lpar2 -KO also attenuated blood flow recovery after femoral artery ligation with decreased vascular density in gastrocnemius. Our study revealed that Lpar2 was mainly expressed and altered in cardiac endothelial cells during MI, and use of endothelial-specific Lpar2 knockout mice phenocopied the global knockout mice. Additionally, adenovirus- Lpar2 and pharmacologically activated LPA2 significantly improved heart function, reduced scar size, increased vascular formation, and alleviated early mortality by maintaining vascular homeostasis owing to protecting vessels from leakage. Mechanistic studies demonstrated that LPA-LPA2 signaling could promote endothelial cell proliferation through PI3K-Akt/PLC-Raf1-Erk pathway and enhanced endothelial cell tube formation via PKD1-CD36 signaling. Conclusions: Our results indicate that endothelial LPA-LPA2 signaling promotes angiogenesis and maintains vascular homeostasis, which is vital for restoring blood flow and repairing tissue function in ischemic injuries. Targeting LPA-LPA2 signal might have clinical therapeutic potential to protect the heart from ischemic injury.